Exploring the phenotypic and molecular diversity of Calendula officinalis L. cultivars featuring varying flower types - Aleksandra Nucia; Tomasz Ociepa; Beata Król; Sylwia Okoń (PeerJ)
Pot marigold is an ornamental plant of great importance in pharmacy and cosmetology. However, there is limited published information on the diversity of the species at both the morphological and genetic levels. This paper aimed to determine the morphological and genetic diversity of selected marigold varieties. The research focused on varieties with different flower colours, and the most important morphological features of flowers and plant height were analysed. Genetic diversity analyses were performed using start codon target (SCoT) markers. The correlation coefficients between the analysed morphological features of the studied marigold varieties showed a significant positive relationship between plant height, the number of inflorescences per plant and inflorescence diameter. Genetic analyses grouped the studied varieties according to the colour of their flowers. The results obtained in our work indicate that, despite the variability observed in morphological features, the gene pool of the analysed marigold varieties is limited. This information can be valuable for marigold breeders, particularly for selecting varieties suitable for crossbreeding in breeding programs. Additionally, it offers insights into the genetic resources of the species and highlights the importance of their bioconservation.